Proceedings of the International Seminar on Promoting Local Resources for Sustainable Agriculture and Development (ISPLRSAD 202 2021
DOI: 10.2991/absr.k.210609.025
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Side Product of the Oil Palm Plant as Animal Feed in Aceh Tamiang District, the Province of Aceh

Abstract: The province of Aceh is one of the provinces that prioritizes the development of palm oil commodities for the plantation sector. In the development of oil palm, the secondary products that can be produced are in the form of oil palm fronds. One of the problems faced in the development of cattle is the availability of feed, especially in the dry season, the lack of knowledge of the farmers about the benefits of palm oil by-products. Meanwhile, consumers' demand for meat from time to time continues to increase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Previous research conducted by Yusriani et al [5] taking place in Karang Baru District, Aceh Tamiang Regency showed that the by-product potential that had not been utilized was 2,718.23 tons/year and a carrying capacity of 2,384.41 (ST/year) for cattle and buffalo. This is an opportunity for the development of beef cattle in the district.…”
Section: Introductionmentioning
confidence: 98%
“…Previous research conducted by Yusriani et al [5] taking place in Karang Baru District, Aceh Tamiang Regency showed that the by-product potential that had not been utilized was 2,718.23 tons/year and a carrying capacity of 2,384.41 (ST/year) for cattle and buffalo. This is an opportunity for the development of beef cattle in the district.…”
Section: Introductionmentioning
confidence: 98%